2013
DOI: 10.12659/ajcr.883739
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous splenic rupture: A rare life-threatening condition; Diagnosed early and managed successfully

Abstract: SummaryBackground:Splenic rupture is a potentially life-threatening condition, often associated with chest or abdominal trauma. Spontaneous rupture is very rare and is usually reported as being secondary to underlying pathological conditions.Case Report:We discuss the case of a 56 year old man who presented with sudden onset left-sided abdominal pain, with no history of trauma.Conclusions:A computed tomography (CT) of the abdomen revealed a ruptured spleen with free fluid in the abdomen. Conservative managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 4 publications
(7 reference statements)
0
23
0
2
Order By: Relevance
“…Therefore, we hypothesized that SSR may present with a different clinical and sonographic pattern and may have a different prognosis compared to TSR. The etiology, symptoms, diagnosis, B-mode appearance, treatment and clinical course have only been sporadically described for SSR 2 3 4 . Furthermore, to the best of our knowledge, there is no description of CEUS patterns of SSR in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we hypothesized that SSR may present with a different clinical and sonographic pattern and may have a different prognosis compared to TSR. The etiology, symptoms, diagnosis, B-mode appearance, treatment and clinical course have only been sporadically described for SSR 2 3 4 . Furthermore, to the best of our knowledge, there is no description of CEUS patterns of SSR in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A patient with infectious mononucleosis and splenic enlargement (splenomegaly) should be closely monitored. The pathologic splenic rupture is the most common cause of death in patients with infectious mononucleosis [4]. It has been believed that increased intra-abdominal pressure or diaphragmatic contraction during severe coughing, vomiting, and defecation, which leads to pressure on the spleen, is the cause of this type of splenic rupture [8].…”
Section: Discussionmentioning
confidence: 99%
“…Several grading systems have been established for splenic rupture based on CT scan or ultrasound ndings and each has been found to be effective in contributing to management and decision making. [4] However, there have been tremendous amount of case reports of atraumatic splenic rupture, there are not any comprehensive assessment to reveal the incidence rate, causes, speci c symptoms, available management methods, and the prognosis. [3]…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a diagnosis of a ruptured spleen is frequently not considered in the absence of trauma, even in the presence of pain in the upper left quadrant and hemodynamic instability, which can lead to devastating outcomes [18] . In these instances, the use of diagnostic tools may greatly increase an accurate diagnosis of atraumatic splenic rupture.…”
Section: Discussionmentioning
confidence: 99%